An integrated model to design earthquake resistant structures - Nourbakhsh, Mehdi (2012)
Selection of the material and design of earthquake resistance structures are an important issue today. Many people die every year due to inappropriate design and selection of the materials. There are several software to be used for structural design of buildings, however they just design the structure based on some limited standards. There is a need to develop a computer-based earthquake resistant design model to integrate the current market’s software with different design standards of different countries. The objective of this study is to propose a model to integrate the local structural design standards/codes with available market’s programs. To achieve this objective, Microsoft Excel was used as the core of the model to be integrated with one of the market’s program. Then, the model was developed in three phases. To test the model, the Iranian design standard (Code 2800) was used to design a 7-story apartment. The results show that the model can be fully integrated with those market’s programs which support Microsoft Excel. The result of Phase 1 of the model is useful to select the optimum selection of the material while Phase 2 and 3 contribute to design of the earthquake resistant structure.